Does auditor tenure improve audit quality? Moderating effects of industry specialization and fee dependence - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2010)
We investigate whether the relation between auditor tenure and audit quality is conditional on auditor specialization and fee dependence. Although prior studies have investigated the relation between extended auditor-client tenure and audit quality, none has examined how this relation is jointly influenced by both auditor specialization and fee dependence. Our main analyses, using accrual quality as a measure of audit quality, show that firms audited by specialists (vs. non-specialists) have relatively higher audit quality with extended auditor tenure, and that this relation is negatively moderated by auditors’ fee dependence on clients. These results are robust to sensitivity tests, and alternative proxies for audit quality such as the issuance of going concern opinions and the market’s response to quarterly earnings surprises.